(untitled) (Archaeologia Adriatica, 2020)
Myth has it that Ajax the Lesser (son of Oileus and also known as Locrian) was killed in a storm on the Gyraean Rocks. Scholars have been trying to locate the rocks ever since Classical Antiquity: from Euboea and Cape Caphareus across Andros and Tênos all the way to Myconos. Their location has remained unknown not so much because it was part of a mythical rather than real geography but rather because with time it has faded into oblivion. Ajax the Lesser was a "threshold creature", one of the figures that symbolises the crossing from this world into the otherworld, who later entered heroic epics as a "historical" hero who fought at Troy, known for his desecration and crimes for which the gods punished him by sending a storm against him as he returned from Troy.